Synthesis and Characterization of Antimicrobial Metal Based Polymeric Ligand Derived from 4,4’-Methylene-bis(furfuraldehyde) - Mughal, M.A.; Mughal, Akhtar; Zuhra Memon, G.; Y. Khuhawar, Mohammad (Asian Journal of Chemistry, 2013)
The present study examines synthesis of a new monomer, 4,4'-methylene-bis(furfuraldehyde), by a general method. The monomer was further condensed with a 1,3-propylenediamine in (1:1) molar ratio to yield a Schiff base polymer ligand poly(4,4'-methylene-bis(furfuraldehyde)-1,3-propylenediimine (PMBFPR). The monomer (MBF) was prepared by the reaction of furfuraldehyde with 1,3,5-trioxane in the presence of acetic acid. The Schiff base polymer (PMBFPR) was found to react readily with Cu(II) acetate monohydrate and Ni(II) acetate, yielding polymer metal complexes (PMBFPRCu) and (PMBFPRNi) respectively. The monomer (MBF), the polymer (PMBFPR) and the polymetal chelates, (PMBFPRCu) and (PMBFPRNi) were characterized by elemental micro analysis, FT-IR, 1H NMR, ultraviolet visible spectrophotometry, thermal analysis and viscosity measurements. The newly synthesized polymer and polymer metal complexes were screened against various microorganisms. For antibacterial activity Shigella flexneri, Micrococcus flavus, Staphylococcus aureus, Bacillus Cirroflgellosus, Escherichia Coli and for antifungal activity Candida albicans, A. Niger, Aspergillus flavus, were investigated by using 'agar well diffusion method'.